Dry storage at two temperatures and three lengths of Polo rose stems - Quevedo-González, Armando; Arriaga-Frías, Alberto; de la Cruz-Guzmán, Gumercindo Honorato; Mandujano-Piña, Manuel (Revista Mexicana de Ciencias Agrícolas, 2025)
Low temperature and hydration of flower stems is associated with increased vase life. Stem length is linked to differences in absorption rate related to anatomical characteristics of vascular ducts. This study aimed to evaluate the effect of two temperatures (4 and 22 °C) and three flower stem lengths (0, 2 and 20 cm) on the postharvest life of Polo roses. In August 2018, Polo rose stems wrapped in kraft paper and plastic bags were divided into two batches that were stored for four days at 22 °C and 4 °C and then subdivided into three groups that were trimmed to 0, 2 and 20 cm in the basipetal direction and placed in a tap water solution to evaluate the vase life. An anatomical description of the three stem lengths was made to determine the xylem vessel diameter, vulnerability and hydraulic conductivity. The results showed that both the application of 4 and 22 °C resulted in a lower rate of water absorption throughout the trial. The flower opening did not differ in 10 of 13 d but was lower with 0 cm stems, with a vase life greater than three days in the 4 °C treatment compared to 2 and 20 cm stems. A lower potential susceptibility to cavitation was determined in 0 cm stems, with vessel elements of 8.65 μm diameter compared to 25.17 μm in longer stems.
Keywords: absorption rate; dry management; flower stem anatomy; xylem vulnerability